Work‐related attitudes: A comparison of Estonia and Finland - Alas, Ruth; Edwards, Vincent (Journal of Business Economics and Management, 2005)
Although Estonia and Finland are culturally related, according to an empirical study in the electronics industry in the two countries they display significant differences in job‐related attitudes. This paper investigates employees’ attitudes toward society, trade unions, work, employer organisations and pay determinants in the two countries from an institutionalist and cultural perspective. While Finland has experienced almost a century of capitalism and democracy, work‐related attitudes in Estonia have been particularly affected by the 50 years of Soviet rule. It is argued that the differences in work‐related attitudes are influenced inter alia by differences in levels of institutional development. First published online: 14 Oct 2010